Evaluating the psychometric properties of a scale to measure intercultural effectiveness - Arslan, Serhat (2015)
The aim of this research is to examine the validity and reliability of the Turkish version of The Intercultural Effectiveness Scale (IES; Portalla & Chen, 2010). The sample of this study consisted of 352 (199 female and 153 male) students. The results of confirmatory factor analysis demonstrated that the 20 items loaded on five factors and the five-dimensional model was well fit (x²= 370.10, df= 152 p= .00, RMSEA= .064, NNFI= .94, CFI= .95, IFI= .95, NFI= .92, RFI= .90, GFI= .91 and SRMR=.066). The overall internal consistency coefficient of the scale was .83. The corrected item-total correlations of IES ranged from .27 to .68. Overall findings demonstrated that this scale had high validity and reliability scores. Nevertheless, further studies that will use IES are important for its measurement force.